2017
DOI: 10.1038/ncomms14855
|View full text |Cite
|
Sign up to set email alerts
|

High resolution analysis of tropical forest fragmentation and its impact on the global carbon cycle

Abstract: Deforestation in the tropics is not only responsible for direct carbon emissions but also extends the forest edge wherein trees suffer increased mortality. Here we combine high-resolution (30 m) satellite maps of forest cover with estimates of the edge effect and show that 19% of the remaining area of tropical forests lies within 100 m of a forest edge. The tropics house around 50 million forest fragments and the length of the world's tropical forest edges sums to nearly 50 million km. Edge effects in tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
159
1
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(189 citation statements)
references
References 38 publications
1
159
1
6
Order By: Relevance
“…Recent estimates suggest 70% of the world's forests are within 1 km of a forest edge (Haddad et al 2015), and that 19% of tropical forests are <100 m from an edge (Brinck et al 2017). The severe convection event that occurred in our study region caused an overall loss of approximately 0.3 Tg C in the study area (0.14 in second-growth forest and 0.16 in oldgrowth forest).…”
Section: Effects Of Fragmentation On Wind Damagementioning
confidence: 75%
“…Recent estimates suggest 70% of the world's forests are within 1 km of a forest edge (Haddad et al 2015), and that 19% of tropical forests are <100 m from an edge (Brinck et al 2017). The severe convection event that occurred in our study region caused an overall loss of approximately 0.3 Tg C in the study area (0.14 in second-growth forest and 0.16 in oldgrowth forest).…”
Section: Effects Of Fragmentation On Wind Damagementioning
confidence: 75%
“…In response to a changing climate, soil warming experiments provide strong empirical support for the hypothesis that increases in global temperatures will stimulate the rate of soil carbon losses, driving a positive carbon‐climate feedback that could accelerate rates of global warming (Crowther et al, ). Furthermore, fragmentation represents a key landscape disturbance and the observations of soil respiration and temperature gradients with proximity to forest edges described in this study add to a growing body of literature pointing to the high capacity of forest fragmentation to alter forest carbon cycling (Bowering et al, ; Briber et al, ; Brinck et al, ; Reinmann & Hutyra 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Using 30‐m‐resolution, satellite‐derived maps of forest cover, Brinck et al . () reported that increased tree mortality near tropical forest edges caused an additional 0.34 Gt of C emissions annually, representing 31% of the current estimated C releases attributed to tropical deforestation. The key mechanisms responsible for the reductions in C stocks in tropical edges include increased desiccation stress, fire, parasitic liana proliferation, and blow down of large trees due to greater exposure to wind (Laurance et al .…”
Section: The Terrestrial C Cyclementioning
confidence: 99%